Magnetic Field Influence on The Properties of Water Treated by Reverse Osmosis - Karkush, M. O.; Ahmed, M. D.; Al-Ani, S. M. A. (Engineering, Technology & Applied Science Research, 2019)
The current study is focused on reviewing the rapid growing of magnetic water use in different science fields and in measuring the influence of several intensities of magnetization on the chemical and electrical properties of tap water treated by reverse osmosis. This work includes water circulation for 24h in magnetic fields of intensities 500, 1000, 1500, and 2000G. The magnetization of water increases some ions in the water such as Mg, K, Na, Cl, and SiO2and decreases Ca and SO3. The main application of magnetic water is the improvement of the geotechnical properties of soft and swelling soil through precipitation of calcite in pores which increases the bond between soil particles and the strength of the soil.